Effect of 6-benzylaminopurine Treatments on Post-harvest Quality and Storage Life of Jamun (Syzygium cumini Skeels) Fruit - Akash Kanaujia; Kalyan Barman; Pooja Belwal; Nitin Yadav; Soni Kushwaha; Amit Kushwaha (Archives of Current Research International, 2025)
Syzygium cumini (Skeels.), commonly known as Jamun, Java plum, or black plum, is a bioactive-rich fruit recognized for its high concentrations of antioxidants, vitamins, and phytochemicals, including hydrolysable tannins, flavonoids, anthocyanins, gallic acid, and quercetin. Despite its nutritional and pharmacological significance, the fruit exhibits a notably short post-harvest shelf life of approximately 3–4 days under ambient conditions. This rapid perishability hinders effective storage, transportation, and commercialization, often resulting in considerable post-harvest losses. This study evaluated the impact of 6-benzylaminopurine (BAP) on extending shelf life and preserving the quality of fully ripe fruit under cold storage. Fruits were dipped in 6-benzylaminopurine (BAP) solutions (0.5, 1.0, and 1.5 mM), air-dried, and stored at 7 ± 1°C in low-density polyethylene (LDPE) bags. Two control groupsdistilled water-treated fruits in open LDPE bags and untreated fruits in sealed LDPE bagswere also included. The result demonstrated that the 1.5 mM 6-benzylaminopurine (BAP) treatment was most effective, significantly reducing spoilage and maintaining key physicochemical attributes. These findings demonstrate the potential of 6-benzylaminopurine (BAP), particularly at 1.5 mM, as a post-harvest treatment to enhance storability, reduce losses, and improve the commercial viability of jamun upto the 30 days after storage. By extending shelf life and minimizing losses, this approach can improve the availability of jamun to consumers and support its commercial viability. The results underscore the potential of 6-benzylaminopurine (BAP) as a post-harvest treatment to address storage challenges for perishable tropical fruits like jamun, contributing to reduced food waste and enhanced marketability.